2021
DOI: 10.1155/2021/7459593
|View full text |Cite|
|
Sign up to set email alerts
|

Influence and Effect of Acupoint Application of Chinese Medicine on Height and Bone Age of Children with Short Stature

Abstract: Objective. To explore the effect of acupoint application of Chinese medicine on children’s height and bone age. Methods. Altogether, 120 children with a short stature treated in our hospital from September 2017 to September 2018 were divided into the control group (CG, n = 60) and the observation group (OG, n = 60) according to the random number table method. The children in CG were given healthy diet and exercise plans and supplemented with daily vitamin intake. The OG was treated with acupoint application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This could stimulate height growth by stimulating the bones of the knee, tibia, and ankle. ST36 (Zusanli) is the most frequently selected acupoint and has been also used for the treatment of short stature in other studies [ 22 , 23 ]. SP6 (Sanyinjiao)is an acupoint where the three yin meridians of the liver, spleen, and kidney meet, and is used to tonify the liver, spleen, and kidney.…”
Section: Discussionmentioning
confidence: 99%
“…This could stimulate height growth by stimulating the bones of the knee, tibia, and ankle. ST36 (Zusanli) is the most frequently selected acupoint and has been also used for the treatment of short stature in other studies [ 22 , 23 ]. SP6 (Sanyinjiao)is an acupoint where the three yin meridians of the liver, spleen, and kidney meet, and is used to tonify the liver, spleen, and kidney.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%